Merdeka Belajar Policy to Improve the Quality of Education - Marzuqi, Badrul Munir; Arifah, Siti Latif (Proceeding International Conference on Education, 2025)
"Bebas Belajar" is a new policy program of the Ministry of Education and Culture of the Republic of Indonesia, initiated by Minister of Education and Culture Nadiem Anwar Makarim. Nadiem has a reason for pursuing an independent learning policy. The 2019 Program for International Student Assessment (PISA) showed that Indonesian students ranked sixth from the bottom; Indonesia ranked 74th out of 79 countries in mathematics and literacy. There are four main points of the new policy of the Ministry of Education and Culture of the Republic of Indonesia, namely: 1) The National Examination (UN) is replaced by the Minimum Competency Assessment and Character Survey. 2) The National Standardized School Examination (USBN) is handed over to schools. 3) Simplification of the Learning Implementation Plan (RPP). 4) Expansion of the zoning system in the admission of new students (PPDB). The characteristics of independent learning include: 1) Development of Soft Skills and Character. 2) Focus on essential materials. 3) Flexible learning. The implementation of independent learning is applied in three options, namely: 1) Independent learning. 2) Independent change. 3) Independent sharing. Implementation of independent learning To be effective and appropriate in its implementation, thorough preparation is needed, including the capacity of human resources must also be prepared as well as possible by gaining complete knowledge about the independent learning policy through the socialization process, gradually but continuously improving teaching methods by introducing student-friendly learning strategies, improving the pedagogical quality of teachers and changing the way of thinking and old paradigms of teachers. The independent campus policy is a continuation of the independent learning concept. The MBKM policy includes: 1) Collaboration Mechanism between PTKIS and Study Programs with external parties. 2) Acceleration of PTN Go International with the PTN Legal Entity (PTN-BH) policy. 3) Internship Mechanism Outside the Study Program.